The "djunta-mon" in the periphery of Lisbon: Cape Verdean migration and moral behavior in a context of urban conflict - Cuberos-Gallardo, Francisco José (Revista de Antropología Social, 2019)
The djunta-mon is a traditional practice of mutual aid that Cape Verdean migrants have adapted to their experience in the periphery of Lisbon. In this article we analyze the new uses, forms and functions that the djunta-mon assumes in the migratory context. For this purpose, the case of Cova da Moura is taken as a neighborhood affected by serious social and urban problems and inhabited mainly by people of Cape Verdean origin. It is noted that the practice of djunta-mon in this neighborhood is part of a broader process of reaffirmation of ethnic identity, which in turn makes sense in a context of strong urban conflict. The results indicate that, in these conditions, the djunta-mon undergoes notable modifications in its forms and functions, which allow it to operate as a broad system of moral references for the Cape Verdean ethnic group.
Keywords: Cape Verdean migration; urban conflict; ethnicity; moral behaviour; mutual aid; Lisbon